2016
DOI: 10.1159/000446017
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from Choriocarcinoma Syndrome Associated with a Metastatic Extragonadal Germ Cell Tumor Hemorrhage

Abstract: A germ cell tumor is the most common form of malignancy in early male life, and can be classified as either seminomatous or nonseminomatous. Choriocarcinoma, comprised of nonseminomatous germ cells, is the most aggressive type of germ cell tumor and characteristically metastasizes to the retroperitoneal lymph nodes and less frequently to the lungs, liver, bone or brain [Shibuya et al., 2009;48: 551–554]. A 56-year-old man was admitted to another hospital complaining of abdominal distension. Symptoms included a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Urgent surgical exploration has been usually performed in a handful of similar cases reported in the literature. Komori et al [ 4 ] reported on the surgical management of hemoperitoneum caused by spontaneous rapture of a mixed germ cell tumor metastatic retroperitoneal lymph node mass penetrating the retroperitoneum between the ligament of Treitz and the inferior mesenteric vein. The patient had considerably high β-HCG and α-FP levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urgent surgical exploration has been usually performed in a handful of similar cases reported in the literature. Komori et al [ 4 ] reported on the surgical management of hemoperitoneum caused by spontaneous rapture of a mixed germ cell tumor metastatic retroperitoneal lymph node mass penetrating the retroperitoneum between the ligament of Treitz and the inferior mesenteric vein. The patient had considerably high β-HCG and α-FP levels.…”
Section: Discussionmentioning
confidence: 99%
“…Despite significant intraoperative blood loss approximately 2 L, complete hemostasis has been accomplished with the patient withstanding the surgical procedure. Unfortunately, the patient died one month later because of massive gastrointestinal hemorrhage [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is evident in a case of pulmonary hemorrhage that was successfully managed with lobectomy and prompt surgical intervention [ 11 ]. Moreover, Komori et al reported a case with metastatic extragonadal germ cell tumor who presented with hemoperitoneum that was treated surgically [ 12 ]. In our case, there were no well-defined culprit vessels to embolize or treat surgically.…”
Section: Discussionmentioning
confidence: 99%
“…Six of the 21 patients with follow-up information died, with a mean time to death of 25 days. Four of deaths were in patients diagnosed with choriocarcinoma, a more aggressive GCT associated with extensive metastasis and varied complication including massive hemorrhage [ 5 , 22 ].…”
Section: Discussionmentioning
confidence: 99%